Specific, sensitive and rapid detection of human plasmodium knowlesi infection by loop-mediated isothermal amplification (LAMP) in blood samples - Lau, Yee Ling; Fong, Mun Yik; Mahmud, Rohela; Chang, Phooi Yee; Palaeya, Vanitha; Cheong, Fei Wen; Chin, Lit Chien; Anthony, Claudia N.; Al-Mekhlafi, Abdulsalam M.; Chen, Yeng (BioMed Central, 2011)
Background: The emergence of Plasmodium knowlesi in humans, which is in many cases misdiagnosed by microscopy as Plasmodium malariae due to the morphological similarity has contributed to the needs of detection and differentiation of malaria parasites. At present, nested PCR targeted on Plasmodium ssrRNA genes has been described as the most sensitive and specific method for Plasmodium detection. However, this method is costly and requires trained personnel for its implementation. Loop-mediated isothermal amplification (LAMP), a novel nucleic acid amplification method was developed for the clinical detection of P. knowlesi. The sensitivity and specificity of LAMP was evaluated in comparison to the results obtained via microscopic examination and nested PCR. Methods: LAMP assay was developed based on P. knowlesi genetic material targeting the apical membrane antigen-1 (AMA-1) gene. The method uses six primers that recognize eight regions of the target DNA and it amplifies DNA within an hour under isothermal conditions (65 degrees C) in a water-bath. Results: LAMP is highly sensitive with the detection limit as low as ten copies for AMA-1. LAMP detected malaria parasites in all confirm cases (n = 13) of P. knowlesi infection (sensitivity, 100) and none of the negative samples (specificity, 100) within an hour. LAMP demonstrated higher sensitivity compared to nested PCR by successfully detecting a sample with very low parasitaemia (< 0.01). Conclusion: With continuous efforts in the optimization of this assay, LAMP may provide a simple and reliable test for detecting P. knowlesi malaria parasites in areas where malaria is prevalent.